A review of research literature on obstacles that prevent use of ICT in pre-service teachers' educational courses - Mirzajani, Hassan; Mahmud, Rosnaini; Mohd Ayub, Ahmad Fauzi; Wong, Su Luan (Australian International Academic Centre, 2015)
In spite of growing amount of technologies, tools and information communication and technology (ICT) by providing pre-service teacher education courses, pre-service teachers' ICT utilization is not still as predicted. Research shows many barriers influencing pre-service teachers’ utilization of ICT. Many researchers have identified a number of factors to describe why student teachers do not feel ready to use ICT in their classrooms. The purpose of this review of research literature is to discover what reasons are key obstacles that prevent utilization of ICT in pre-service teachers’ educational courses. The review results show that most of the researchers believe that lack of enough training, lack of suitable software and hardware, lack of knowledge and skills, lack of ICT leadership support, lacking time, and lack of self-efficacy are the key barriers for utilization of ICTs in pre-service teachers’ educational courses. The study also concluded that understanding the amount to which these obstacles affect ICT users and institutes can support decision-making on how to equip them.